Pengaruh Penggunaan Tris Dalam Pengencer Susu Skim Terhadap Resistensi Spermatozoa Sapi Simmental Pasca Pembekuan - Hoesni, Fachroerrozi (Fakultas Peternakan Universitas Jambi, 2016)
This study aimed to determine the effect of the use of tris in skim milk diluent in immune Simmental cattle spermatozoa after freezing. Randomized block design with 5 treatments and 6 blocks of ejaculation was applied. The treatments were P0 = 93% skim milk diluent without tris + + 7% glycerol, P1 = 83% skim milk diluent tris + 10% + 7% glycerol, P2 = 73% skim milk diluent tris + 20% + 7% glycerol, P3 = skim milk diluent tris 63% + 30% + 7% glycerol, P4 = skim milk diluent trsi 53% + 40% + 7% glycerol. The results showed that the use of skim milk diluent tris in the P2 treatment exert a highly significant (P <0.01) in maintaining the survival of spermatozoa after freezing Simmental cattle. The results of this study concluded that the use of tris in skim milk dilution to the extent of 20% to maintain the vitality of spermatozoa after freezing Simmental cattle.